Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Snowball Throwing dengan Media TTS pada Pembelajaran IPA Kelas IV SD Negeri 02 Koto Bangun Kecamatan Kapur IX - Elimasni Elimasni (Pendidikan Biologi FKIP UMMY, 2019)
Based on preliminary observations in class IV of SD Negeri 02 Koto Bagun, Kapur IX District, problems of science learning were found. The teacher is less varied, creative in teaching in class, only emphasizes the delivery of material and assignments. Students are less involved in learning, less enthusiastic, less motivated in discussion activities, and the use of learning media is not optimal. Formulation of the research problem